Comparative evaluation of the main parameters of racing distances of the largest international and all-russian competitions in modern road cycling - Kubeev, A. V.; Oganesyan, A. A.; Savenkova, E. A.; Matina, V. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a comparative assessment of the difficulties of the racing distances of the largest international and Russian road cycling competitions.